Hypersensitivity Reactions to Gadolinium‐Based Contrast Agents: Update From an Allergist's Point of View - Francesca Losa; Giovanni Paoletti; Giulia Costanzo; Fabio Lodi Rizzini; Marina Mauro; Donatella Preziosi; Federica Rivolta; Andrea Sangalli; Andrea Toniato; Serena Traversi; Alessandro Vrenna; Mario Di Gioacchino; et al. (Clinical and Translational Allergy)
ABSTRACT Background The increasing use of Magnetic Resonance Imaging (MRI) has led to a rise in the administration of gadolinium‐based contrast agents (GBCAs), accompanied by a growing number of reported adverse events (AEs). Objective This review aims to provide an updated overview of hypersensitivity reactions (HSRs) to GBCAs, focusing on diagnostic and management strategies from an allergological perspective. Methods We reviewed recent literature concerning the classification, clinical presentation, and pathophysiological mechanisms of HSRs to GBCAs. Particular attention was given to current recommendations for diagnosis, risk stratification, and prevention. Discussion Adverse events to GBCAs are categorized into Type A reactions, which are dose‐dependent and predictable, and Type B reactions, which are dose‐independent hypersensitivity reactions. The latter may be allergic or non‐allergic, presenting diagnostic and therapeutic challenges. Conclusions HSRs to GBCAs, though relatively rare, require careful evaluation and tailored management. An allergological work‐up, including skin testing and graded challenges when appropriate, plays a critical role in the safe re‐exposure of patients with prior reactions.